Using osmotic pressure simulations to test potentials for ions. Issue 42 (2nd October 2020) - Gillespie, Colin; Milner, Scott T.
Abstract : This paper presents a new method to simulate the osmotic pressure of an ionic solution. Abstract : This paper presents a new method to simulate the osmotic pressure of an ionic solution. Previous simulation methods confine ions between walls, and the osmotic pressure is inferred from the force required to maintain this confinement. In this work, we impose a harmonic potential on the ions to form a nonuniform concentration profile in the solution. As this profile arises from the force balance of the harmonic potential with the osmotic pressure, it can be used to determine the osmotic pressure across the entire concentration profile. This method can be performed without specialized programming, making it accessible to the general user. Using our method, we find that standard potentials for Na + and Cl − ions need adjustments to be consistent with experimental osmotic pressure at high concentrations.